Pulmonary Disease Secondary to Reflux Mimicking Interstitial Pneumonia in Systemic Sclerosis: Case Report and Literature Review - Ricardo Azêdo de Luca Montes; Nathalia Mazolli Veiga; Pedro Gemal Lanzieri; Luis Otávio Cardoso Mocarzel (Case Reports in Rheumatology)
Systemic sclerosis is a complex disease due to the variety of clinical presentations, often superimposed on other conditions, related or not to the connective tissue. We report a 43-year-old Brazilian woman with limited systemic sclerosis and pulmonary symptoms secondary to gastroesophageal reflux disease, with a clinical presentation similar to a diffuse interstitial lung disease. Because of the frequency of interstitial lung injury due to systemic sclerosis, this was an important differential diagnosis, which could be excluded after optimized treatment of reflux disease, with clinical and radiological improvement. Clinical management of patients with collagen diseases requires clinician skills to identify the natural history and understand its nuances. This is a common situation in clinical practice, but with a few discussions in international literature.